Properties of internal (chemical) pressure in superconducting YBa₂Cu₃O₇₋y perovskite created by oxygen - Khirnyi, V.F. (Functional Materials, 2014)
The properties of internal (chemical) pressure Pi in superconducting YBa₂Cu₃O₇₋y perovskite are analytically investigated. Predicted are the values of the critical temperature Tc for the main crystallographic axes, the change of the value of dTc/dPi and the possibility to obtain YBa₂Cu₃O₇₋y samples with Tc = 166.7 K.